2008
DOI: 10.1083/jcb.200808027
|View full text |Cite
|
Sign up to set email alerts
|

Sarcospan reduces dystrophic pathology: stabilization of the utrophin–glycoprotein complex

Abstract: Mutations in the dystrophin gene cause Duchenne muscular dystrophy and result in the loss of dystrophin and the entire dystrophin–glycoprotein complex (DGC) from the sarcolemma. We show that sarcospan (SSPN), a unique tetraspanin-like component of the DGC, ameliorates muscular dystrophy in dystrophin-deficient mdx mice. SSPN stabilizes the sarcolemma by increasing levels of the utrophin–glycoprotein complex (UGC) at the extrasynaptic membrane to compensate for the loss of dystrophin. Utrophin is normally restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
85
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(90 citation statements)
references
References 35 publications
5
85
0
Order By: Relevance
“…39,62,63 Loss of sarcospan in mice does not result in muscular dystrophy, 64 though overexpression in mdx muscles can reduce disease. 16 Loss of sarcoglycans can also alter the stability of dystroglycan and dystrophin in skeletal muscle, 39,55 though these proteins are still present on the sarcolemmal membrane. 39,55,65 By contrast with sarcospan, loss of dystrophin (in the mdx mouse) results in muscular dystrophy, 35,36,66 as does loss of dystroglycan specifically in skeletal muscle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…39,62,63 Loss of sarcospan in mice does not result in muscular dystrophy, 64 though overexpression in mdx muscles can reduce disease. 16 Loss of sarcoglycans can also alter the stability of dystroglycan and dystrophin in skeletal muscle, 39,55 though these proteins are still present on the sarcolemmal membrane. 39,55,65 By contrast with sarcospan, loss of dystrophin (in the mdx mouse) results in muscular dystrophy, 35,36,66 as does loss of dystroglycan specifically in skeletal muscle.…”
mentioning
confidence: 99%
“…Such targets cut a wide swath across aspects of muscle biology, ranging from inhibitors of apoptosis (eg, Bcl-2 1 ) to stimulators of muscle growth and regeneration (eg, myostatin inhibitors, [2][3][4][5] Igf1 6 ) to inducers of, or members of, alternative transmembrane protein complexes (eg, utrophin, [7][8][9] agrin, 10 -12 neuregulin, 13 integrin ␣7B, 14,15 sarcospan, 16 ADAM12, 17,18 and Galgt2 19 -21 ). This last category contains a glycosyltransferase, Galgt2, which can alter the expression and properties of membrane proteins in skeletal muscle.…”
mentioning
confidence: 99%
“…Muscle function is compromised by the destabilization of the sarcolemma, a result of dystrophin deficiency (2), rendering skeletal muscle susceptible to contraction-induced injury (26). Without a cure, strategies to mitigate the disease progression and improve muscle function have been developed to compensate for dystrophin deficiency by boosting the presence of dystrophin-like cytoskeletal proteins (5,15,17,25). Specifically, utrophin, a protein homologue of dystrophin, sufficiently compensates for dystrophin and improves the phenotype of mdx mice, the primary animal model for DMD (11,28,30,33).…”
mentioning
confidence: 99%
“…Previous studies showed the utrophin–glycoprotein complex (UGC) did not compensate for the loss of dystrophin, and overexpression of utrophin of α7β1 integrin alone could not fully rescue the dystrophic symptoms [86]. Transgenic expression of sarcospan ( SSPN ) increased UGC and α7β1 integrin sarcolemmal expression and ameliorated DMD pathology [87, 88]. Overall, these results suggest the upregulation of both adhesion complexes and sarcospan would increase the therapeutic potential compared with a single component.…”
Section: Introductionmentioning
confidence: 92%